Impact of Packaging Factors on Consumer Purchase Decision of Energy Drinks in Nepal - Pandey, Bomlal (Dibyajyoti Journal, 2024)
Innovation in packaging relies heavily on connections within the research and development community and the packaging supply chain. This study explore the impact of the factors of packaging, which includes design, labels, innovation, and brand image on the consumer purchase decision of the energy drinks in case of Nepal. In this study descriptive and causal-comparative research design has used. The population and sample has based on primary sources, with a sample size of 400 respondents. Data has collected through a structured questionnaire, which includes demographic information and a Likert scale measuring the impact of various factors on consumer decision. The data is analyzed using SPSS tools, including mean, standard deviation, correlation, and regression. Microsoft Excel sheets has used for data collection procedures and tables as required. The study has provides a comprehensive view of the relationships between packaging design, innovation, labeling, and brand image and their impact on consumer purchase decisions. People are inclined to obtain food information through images in packaging. The findings underscore the critical role that packaging design, innovation, labeling, and brand image play in shaping consumer perceptions and driving purchase decisions. The positive correlations identified between packaging attributes and consumer purchase decisions highlight the importance of investing in packaging optimization efforts. In conclusion, market landscape, energy drink brands can leverage packaging design and innovation as a pivotal differentiating factor. By focusing on creating a packaging experience that is both distinct and memorable, brands can secure a competitive edge and establish a lasting connection with consumers.